Cdc42 Regulates Apical Junction Formation in Human Bronchial Epithelial Cells through PAK4 and Par6B - Wallace, Sean W. (The American Society for Cell Biology, 2010)
Cdc42 has been implicated in numerous biochemical pathways during epithelial morphogenesis, including the control of spindle orientation during mitosis, the establishment of apical-basal polarity, the formation of apical cell–cell junctions, and polarized secretion. To investigate the signaling pathways through which Cdc42 mediates these diverse effects, we have screened an siRNA library corresponding to the 36 known Cdc42 target proteins, in a human bronchial epithelial cell line. Two targets, PAK4 and Par6B, were identified as necessary for the formation of apical junctions. PAK4 is recruited to nascent cell–cell contacts in a Cdc42-dependent manner, where it is required for the maturation of primordial junctions into apical junctions. PAK4 kinase activity is essential for junction maturation, but overexpression of an activated PAK4 mutant disrupts this process. Par6B, together with its binding partner aPKC, is necessary both for junction maturation and for the retention of PAK4 at sites of cell–cell contact. This study demonstrates that controlled regulation of PAK4 is required for apical junction formation in lung epithelial cells and highlights potential cross-talk between two Cdc42 targets, PAK4 and Par6B.